2013
DOI: 10.1016/j.vetpar.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of heather (Ericaceae) extracts on different development stages of Teladorsagia circumcincta and Haemonchus contortus

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…This is a first example for which a whole series of consistent results were obtained that covered in vitro assays (e.g. Moreno-Gonzalo et al, 2013), controlled in vivo studies with experimental infections in confined conditions (Frutos et al, 2008;Moreno-Gonzalo et al, 2014) and systemic studies with natural infections (Osoro et al, 2009).…”
Section: Exploring Plant Resources As Nutraceuticals: Example Of Othementioning
confidence: 69%
“…This is a first example for which a whole series of consistent results were obtained that covered in vitro assays (e.g. Moreno-Gonzalo et al, 2013), controlled in vivo studies with experimental infections in confined conditions (Frutos et al, 2008;Moreno-Gonzalo et al, 2014) and systemic studies with natural infections (Osoro et al, 2009).…”
Section: Exploring Plant Resources As Nutraceuticals: Example Of Othementioning
confidence: 69%
“…In this review, antiparasitic effects of plants vary depending on the plant species, stage, the nematode species and the parasitic stage. Erica cinera was more active against eggs and L 3 of T. columbriformis than to inhibit the egg hatching and larvae exsheathment of abomasal parasites ( H. contortus and T. circumcinta ) (Moreno-Gonzalo et al ., 2013 a , 2013 b ). The Agave sisalana and Moringa oleifera has greater ovicidal effect while Acacia nilotica and A. raddiana are more active against L 3 of GIN (Botura et al ., 2013; Zabré et al ., 2017; De Medeiros et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed the anthelmintic potential of the plants rich in condensed tannins. In vitro evaluations demonstrated effects of tanniferous plant extracts on the larval migration, larval artificial exsheathment, adult motility inhibition and egg hatching of H. contortus (Alonso-Díaz et al ., 2008; Moreno-Gonzalo et al ., 2013 a ; Naumann et al ., 2014). The use of polyvinylpolypyrrolidone (PVPP), an inhibitor of tannins, confirmed that this metabolite is responsible for the anthelmintic activity of the tanniferous plants (Alonso-Díaz et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…imperati stolon extract, demonstrating the difference between these extracts (Table 2). Extracts of several plant species are rich in phenolic compounds that inhibit nematode exsheatment [32, 33]. However, few studies have reported different activities among parts of the same plant [34].…”
Section: Resultsmentioning
confidence: 99%